(untitled) (Nativa, 2018)
O estudo avaliou a percepção da população da região de Carajás sobre a influência da exploração dos recursos naturais, envolvendo desmatamento e queimadas, urbanização, alteração no clima e preservação da Floresta Nacional de Carajás sobre a economia e o bem-estar da população local. Aplicou-se a análise multivariada para associar um conjunto amplo de variáveis na definição de indicadores representativos das dimensões ambiental e ecológica. Os resultados indicaram que mais de 80% das pessoas entrevistadas afirmaram ter conhecimento sobre a importância da Flona de Carajás para o desempenho das atividades econômicas e do bem-estar da população do seu entorno. Os indicadores das dimensões ambiental e ecológica foram considerados, por mais de 52% dos entrevistados, como de alta importância para compor o valor econômico total da Flona e contribuir para sua preservação e/ou gestão sustentável. Conclui-se que a população local percebe e qualifica os efeitos das mudanças causadas pela ação antrópica sobre os recursos naturais sobre o desempenho da economia e a qualidade de vida das pessoas. Palavras-chave: economia ambiental, serviços ecossistêmicos, unidade de conservação, Floresta Amazônica. THE IMPORTANCE OF ECOSYSTEM SERVICES FOR ECONOMIC DEVELOPMENT AND SOCIAL WELFARE IN THE POPULATION’S PERCEPTION: THE CASE OF THE CARAJÁS NATIONAL FOREST ABSTRACT: This study evaluates the perceptions of the population residing in the region of Carajás with respect to the natural resource exploitation, deforestation and forest fires, urbanization, climate change and the preservation of the Carajás National Forest, considering the economy and welfare of local the population. Multivariate analysis was applied to associate a wide group of variables with the representative indicators in environmental and ecological dimensions. Interviews with local people indicate that more than 80% of all interviewed are aware of the importance of the Carajás Flona for the development of economic activities and for the population´s welfare in their surroundings. Indicators of environmental and ecological dimensions were regarded by more than 52% of interviewees as being of great importance to the composition the total economic value of Flona and to contribute to preservation or sustainable management. We conclude that the local population adequately perceived and qualified the effects of the changes caused by the anthropic action on the natural resources with respect to the development of economy and the quality of life of the people. Keywords: environmental economics, ecosystem services, conservation unit, Amazon Forest.